2021
DOI: 10.1186/s12873-021-00480-w
|View full text |Cite
|
Sign up to set email alerts
|

Hemogram-derived ratios as prognostic markers of ICU admission in COVID-19

Abstract: Background The vast impact of COVID-19 call for the identification of clinical parameter that can help predict a torpid evolution. Among these, endothelial injury has been proposed as one of the main pathophysiological mechanisms underlying the disease, promoting a hyperinflammatory and prothrombotic state leading to worse clinical outcomes. Leukocytes and platelets play a key role in inflammation and thrombogenesis, hence the objective of the current study was to study whether neutrophil-to-ly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 27 publications
6
26
0
Order By: Relevance
“…NLR is the most studied hematological index in COVID-19 patients and higher values were correlated with disease severity and progression [ 12 , 13 , 23 , 24 , 25 ], death [ 13 , 14 , 22 , 24 , 26 ], and treatment response [ 27 ]. Our observations are in agreement for NLR but also for PLR, MLR, SII, and dNLR and are correlated with results from other studies [ 11 , 12 , 13 , 14 , 15 , 23 , 24 , 25 , 26 , 28 , 29 , 30 , 31 ]. In our study, dynamic changes of these hematological indices had stronger correlations and better predictive value for progression to IMV in non-intubated patients and death compared with ICU admission values.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…NLR is the most studied hematological index in COVID-19 patients and higher values were correlated with disease severity and progression [ 12 , 13 , 23 , 24 , 25 ], death [ 13 , 14 , 22 , 24 , 26 ], and treatment response [ 27 ]. Our observations are in agreement for NLR but also for PLR, MLR, SII, and dNLR and are correlated with results from other studies [ 11 , 12 , 13 , 14 , 15 , 23 , 24 , 25 , 26 , 28 , 29 , 30 , 31 ]. In our study, dynamic changes of these hematological indices had stronger correlations and better predictive value for progression to IMV in non-intubated patients and death compared with ICU admission values.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, this was highlighted by the change in the discriminative power (value of AUC) of these indices over time. AUC values for the derived hematological indices, even the ICU admission values, are roughly in line with the AUC reported in other studies [ 12 , 15 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], but different cut-off values were taken. For example, the cut-off value range for NLR as a predictor for disease severity or death is very wide—from 3.3 to 15.2 [ 12 , 15 , 24 , 27 , 32 ]—making it difficult to establish a final cut-off value.…”
Section: Discussionsupporting
confidence: 87%
“…The results of various studies have shown a link between values of blood factors with high blood pressure [ 29 31 ] and COVID-19 [ 32 ]. Meanwhile, these factors can be considered as predictors of hypertension [ 33 ] or severity of COVID-19 [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another research revealed that neutrophil‐to‐platelet ratio (NPR) had the highest predictive value at ICU admission among COVID‐19 patients in multivariable logistic regression models with NLR, PLR, and SII. 38 Similarly, a study by López‐Escobar et al 8 ( n = 2808) showed NLR and NPR to be significantly and independently associated with in‐hospital mortality of COVID‐19 patients in complex adjusted multivariable regression models.…”
Section: Discussionmentioning
confidence: 94%